Novel BMI cutoff points for obesity diagnosis in older Hispanic adults. - Rodriguez-Tadeo, Alejandra (2024)
Current body mass index (BMI) cutoff points (≥ 30 kg/m2) underestimate obesity prevalence in older adults. The aim of the present study was to propose new BMI cutoff points for identifying obesity in older Hispanic adults. In this study, new internally derived (ID) BMI cutoff point for obesity in older Hispanic adults was developed by analyzing data from the National Health and Nutrition Survey of 2018–2019 from Mexico. To evaluate the performance/validation of this newly proposed cutoff point, data from the "Study of the 1000", conducted in Northern Mexico, was utilized. Sensitivity, and negative predictive value (NPV) were assessed using receiver operating characteristic analysis, with obesity defined by fat mass index (FMI; ≥ 9.0 kg/m2 for men and ≥ 12.0 kg/m2 for women) as the reference method. The newly proposed ID BMI cutoff point was ≥ 27.2 kg/m2 which demonstrated high sensitivity (≥ 99.4%) and NPV (≥ 99.5%) in the total sample. Furthermore, the prevalence of obesity estimated by the new BMI cutoff point was comparable to that estimated by the FMI. The newly proposed BMI cutoff point provides a more accurate identification of obesity in older Hispanic adults. These findings have implications for improving obesity diagnosis and management in this population.